2014
DOI: 10.1108/caer-02-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Yield and economic performance of the use of GM cotton worldwide over time

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…These results were also reported for China (with 67% reduction) for Australia (with 64% reduction) (Witjaksono et al, 2014). Because the Bt genes don't control the sucking pests (aphids, white flies, jassides, and bugs), it was recommended in Burkina Faso to spray two times at 86 and 100 days after cotton emergence.…”
Section: Seed Cotton Yield and Healthy Bolls In Btand Conventional Fimentioning
confidence: 52%
See 1 more Smart Citation
“…These results were also reported for China (with 67% reduction) for Australia (with 64% reduction) (Witjaksono et al, 2014). Because the Bt genes don't control the sucking pests (aphids, white flies, jassides, and bugs), it was recommended in Burkina Faso to spray two times at 86 and 100 days after cotton emergence.…”
Section: Seed Cotton Yield and Healthy Bolls In Btand Conventional Fimentioning
confidence: 52%
“…On average in China, the yield increase due to Bttoxins effectiveness ranged from 31 to 63% (Witjaksono et al, 2014). In the US the yield increase over the past ten years was approximately 33% (Witjaksono et al, 2014). In terms of income, Sankula et al (2005) reported the net benefit of US$74.29/ha for conventional cotton and US$128.85/ha for Btone.…”
Section: Seed Cotton Yield and Healthy Bolls In Btand Conventional Fimentioning
confidence: 99%
“…The total power of agricultural machinery indicates the level of mechanization in cotton production. The utilization of genetically modified Bt cotton enhances yield; considerable evidence suggests that Bt cotton has brought economic benefits to farmers in numerous countries [30]. Starting from the successful development of domestically produced anti-insect cotton (GK) in China in 1994, which effectively eradicates cotton bollworms, the commercial cultivation of insect-resistant cotton was approved by the Ministry of Agriculture in 1997.…”
Section: Conceptual Framework: Determinants Of Cotton Yieldmentioning
confidence: 99%